Demographic and socio-economic changes in the coastal fishing community of India - Syda Rao, G.; Sathianandan, T.V.; Kuriakose, Somy; Mini, K.G.; Najmudeen, T.M.; Jayasankar, J.; Mathew, Wilson T. (Indian Journal of Fisheries, 2016)
The spatial and temporal changes in the demographic and socio-economic indicators of coastal fishing community of India were studied using data collected during the national level census on marine fishermen population in 2005 and 2010, covering 11 maritime states and union territories of the country. Information on population growth, sex ratio, literacy level and educational status, poverty level, sectoral dependency and occupational categories of the coastal fisherfolk were analysed and compared with analogous figures of national averages on these socio-economic indicators. The marine fishermen of India, who depend on fisheries for their subsistence, were significantly below the national averages in many of key demographic indicators. The results of correspondence analysis carried out for visual description of the association of economic status with the key indicators showed that, the below poverty class among fishermen were more associated with low family size compared to large sized families, which implicates to labour supply in a labour demanding socio-economy of marine fisheries. Different dependency ratios were computed as a simple summary measure for comparison of age structure of fisherfolks.